The Role of Isothiocyanates as Cancer Chemo-Preventive, Chemo-Therapeutic and Anti-Melanoma Agents - Melina Mitsiogianni; Georgios Koutsidis; Nikos Mavroudis; Dimitrios T. Trafalis; Sotiris Botaitis; Rodrigo Franco; Vasilis Zoumpourlis; Tom Amery; Alex Galanis; Aglaia Pappa; Mihalis I. Panayiotidis (MDPI AG, 2019)
Many studies have shown evidence in support of the beneficial effects of phytochemicals in preventing chronic diseases, including cancer. Among such phytochemicals, sulphur-containing compounds (e.g., isothiocyanates (ITCs)) have raised scientific interest by exerting unique chemo-preventive properties against cancer pathogenesis. ITCs are the major biologically active compounds capable of mediating the anticancer effect of cruciferous vegetables. Recently, many studies have shown that a higher intake of cruciferous vegetables is associated with reduced risk of developing various forms of cancers primarily due to a plurality of effects, including (i) metabolic activation and detoxification, (ii) inflammation, (iii) angiogenesis, (iv) metastasis and (v) regulation of the epigenetic machinery. In the context of human malignant melanoma, a number of studies suggest that ITCs can cause cell cycle growth arrest and also induce apoptosis in human malignant melanoma cells. On such basis, ITCs could serve as promising chemo-therapeutic agents that could be used in the clinical setting to potentiate the efficacy of existing therapies.